2006
DOI: 10.1111/j.1600-6143.2006.01434.x
|View full text |Cite
|
Sign up to set email alerts
|

Myeloma Responses and Tolerance Following Combined Kidney and Nonmyeloablative Marrow Transplantation: In Vivo and In Vitro Analyses

Abstract: Six patients with renal failure due to multiple myeloma (MM) received simultaneous kidney and bone marrow transplantation (BMT) from HLA-identical sibling donors following nonmyeloablative conditioning, including cyclophosphamide (CP), peritransplant antithymocyte globulin and thymic irradiation. Cyclosporine (CyA) was given for approximately 2 months posttransplant, followed by donor leukocyte infusions. All six patients accepted their kidney grafts long-term. Three patients lost detectable chimerism but acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
207
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(210 citation statements)
references
References 43 publications
(48 reference statements)
2
207
0
1
Order By: Relevance
“…In addition to skin, split tolerance in chimeric canine recipients of heart transplants has also been reported, suggesting that polymorphisms in tissue-specific antigens may not be an exclusive property of the skin [52]. Most recently, clinical trials involving combined kidney transplantation and non-myeloablative BMT were conducted in human patients [53]. Surprisingly, long-term acceptance of donor kidney was not associated with maintenance of donor hematopoietic cells, which, as the authors suggested, may reflect the differential expression of donor antigens that are in fact tissue-specific.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to skin, split tolerance in chimeric canine recipients of heart transplants has also been reported, suggesting that polymorphisms in tissue-specific antigens may not be an exclusive property of the skin [52]. Most recently, clinical trials involving combined kidney transplantation and non-myeloablative BMT were conducted in human patients [53]. Surprisingly, long-term acceptance of donor kidney was not associated with maintenance of donor hematopoietic cells, which, as the authors suggested, may reflect the differential expression of donor antigens that are in fact tissue-specific.…”
Section: Discussionmentioning
confidence: 99%
“…TCR repertoire analysis revealed a diverse T-cell repertoire [83]. Kawai [77] Scandling [80] Scandling [80] Leventhal [83] Buhler [84] Kawai [76] Scandling [79] Leventhal [88] Fudaba [85] Scandling [87] Leventhal [39] Spitzer [86] Scandling [78] nm: not mentioned; TI: thymic irradiation; TLI: total lymphoid irradiation; ATG: antithymocyte globulin; CNI: calcineurin inhibitor; MMF: mycophenolate mofetil; TAC: tacrolimus; MGH: Massachusetts General Hospital.…”
Section: Clinical Translation Of Chimerism-based Transplantation Tolementioning
confidence: 99%
“…The group from Massachusetts General Hospital (MGH) showed tolerance in six patients undergoing simultaneous bone marrow and kidney transplants from human leukocyte antigen (HLA)-identical donors for the treatment of multiple myeloma in patients with renal failure (Fudaba et al 2006). Three patients showed transient donor chimerism, but were successfully weaned off immunosuppression.…”
Section: Mixed Chimerismmentioning
confidence: 99%